PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI BPJS KESEHATAN CABANG BANDAR LAMPUNG - Mutiara, Siska; Candra, Ade (Universitas Nusa Cendana, 2024)
This study aims to analyze the effect of work motivation and discipline on employee performance at BPJS Kesehatan, Bandar Lampung branch. Good employee performance is crucial in achieving organizational goals. Factors such as work motivation, including rewards and incentives, and work discipline, such as punctuality and adherence to company regulations, play an important role in improving productivity. This research uses a quantitative method with data collection through questionnaires distributed to 44 respondents. The results of the analysis show that work discipline has a significant impact on employee performance, while work motivation does not have a significant partial effect. However, simultaneously, both variables have a significant influence on employee performance. Therefore, BPJS Kesehatan is expected to focus more on developing work discipline programs and improving the motivation system to enhance employee performance. Keywords: Work Motivation; Work Discipline; Employee Performance